2021
DOI: 10.1126/science.abd8377
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of bacterial H 2 S biogenesis targeting antibiotic resistance and tolerance

Abstract: Emergent resistance to all clinical antibiotics calls for the next generation of therapeutics. Here we report an effective antimicrobial strategy targeting the bacterial hydrogen sulfide (H2S)–mediated defense system. We identified cystathionine γ-lyase (CSE) as the primary generator of H2S in two major human pathogens, Staphylococcus aureus and Pseudomonas aeruginosa, and discovered small molecules that inhibit bacterial CSE. These inhibitors potentiate bactericidal antibiotics against both pathogens in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
130
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(174 citation statements)
references
References 96 publications
7
130
1
Order By: Relevance
“…Two broadly recognized anti-bacterial host strategies are the induction of oxidative stress, mediated by a myriad of highly reactive, inorganic oxygen- and nitrogen species (ROS and RNS), and copper (Cu) toxicity ( 1 , 2 ). Bacteria upregulate the biogenesis of hydrogen sulfide (H 2 S) in response to ROS- and antibiotic stress, which enhances persistence in biofilms or in cells ( 3 , 4 ), while adaptation to Cu poisoning involves cytoplasmic Cu(I) sensing by specialized Cu(I)-sensing metalloregulatory proteins ( 5–7 ). Cu(I) sensing turns on a transcriptional program to sequester and/or efflux Cu(I) from the cytoplasm of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Two broadly recognized anti-bacterial host strategies are the induction of oxidative stress, mediated by a myriad of highly reactive, inorganic oxygen- and nitrogen species (ROS and RNS), and copper (Cu) toxicity ( 1 , 2 ). Bacteria upregulate the biogenesis of hydrogen sulfide (H 2 S) in response to ROS- and antibiotic stress, which enhances persistence in biofilms or in cells ( 3 , 4 ), while adaptation to Cu poisoning involves cytoplasmic Cu(I) sensing by specialized Cu(I)-sensing metalloregulatory proteins ( 5–7 ). Cu(I) sensing turns on a transcriptional program to sequester and/or efflux Cu(I) from the cytoplasm of cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant effect of short-term adoption of diets either enriched for or deficient in SAAs was observed on relative SRB populations in stool samples from healthy human volunteers [ 32 ]; future studies employing longer-term dietary interventions and greater statistical power are required to further clarify this question. Finally, it has been proposed that bacterial production of H 2 S protects the bacteria against oxidative stress and may contribute to antibacterial resistance [ 33 ]. For example, Shatalin et al [ 33 ] developed novel small molecule inhibitors of bacterial CSE and found these inhibitors improved antibiotic potency against Staphylococcus aureus and Pseudomonas aeruginosa in vitro and in mice, supporting the theory that endogenous production of H 2 S in bacteria might contribute to antibacterial resistance.…”
Section: Biological Generation Of Hydrogen Sulfide (H 2 S)mentioning
confidence: 99%
“…Finally, it has been proposed that bacterial production of H 2 S protects the bacteria against oxidative stress and may contribute to antibacterial resistance [ 33 ]. For example, Shatalin et al [ 33 ] developed novel small molecule inhibitors of bacterial CSE and found these inhibitors improved antibiotic potency against Staphylococcus aureus and Pseudomonas aeruginosa in vitro and in mice, supporting the theory that endogenous production of H 2 S in bacteria might contribute to antibacterial resistance. We believe research using germ-free mice is one approach that may help provide more information regarding the relevance of SRB-derived H 2 S in whole-animal metabolism and physiology.…”
Section: Biological Generation Of Hydrogen Sulfide (H 2 S)mentioning
confidence: 99%
“…The majority of bacterial species whose genomes were completely sequenced have the orthologs of mammalian genes encoding CBS, CSE, or 3MST [ 15 ]. Since H 2 S provides defense against modern antibiotics in bacteria, suppression of H 2 S-producing enzymes in pathogens by new drugs would be a promising antimicrobial treatment strategy [ 15 , 27 ]. The use of H 2 S biogenesis as a target for versatile antibiotic potentiators may have therapeutic potential for the fight against difficult-to-treat infections based on bacterial antibiotic tolerance.…”
Section: Endogenous Production Of H 2 Smentioning
confidence: 99%